The effects of action, normality, and decision carefulness on anticipated regret: Evidence for a broad mediating role of decision justifiability. - REB, Jochen (Institutional Knowledge at Singapore Management University, 2010)
Two distinct theoretical views explain the effects of action/inaction and social normality on anticipated regret. Norm theory (Kahneman & Miller, 1986) emphasises the role of decision mutability, the ease with which one can imagine having made a different choice. Decision justification theory (Connolly & Zeelenberg, 2002) highlights the role of decision justifiability, the perception that the choice was made on a defensible basis, supported by convincing arguments or using a thoughtful, comprehensive decision process. The present paper tests several contrasting predictions from the two theoretical approaches in a series of four studies. Study 1 replicated earlier findings showing greater anticipated regret when the chosen option was abnormal than when it was normal, and perceived justifiability mediated the effect. Study 2 showed that anticipated regret was higher for careless than for careful decisions. Study 3 replicated this finding for a sample holding a different social norm towards the focal decision. Finally, Study 4 found that, when decision carefulness, normality and action/inaction were all specified, only the former showed a significant effect on anticipated regret, and the effect was again mediated by perceived justifiability. Decision justification theory thus appears to provide a better account of anticipated regret intensity in this context than does norm theory.